The association between milk consumption and the metabolic syndrome: a cross-sectional study of the residents of Suzhou, China and a meta-analysis. Issue 9 (22nd January 2020) - Hidayat, Khemayanto; Yu, Lu-Gang; Yang, Jin-Rong; Zhang, Xue-Ying; Zhou, Hui; Shi, Yu-Jie; Liu, Biao; Qin, Li-Qiang
Abstract: The association between milk consumption and the metabolic syndrome remains inconclusive, and data from Chinese populations are scarce. We conducted a cross-sectional study to investigate the association between milk consumption and the metabolic syndrome and its components among the residents of Suzhou Industrial Park, Suzhou, China. A total of 5149 participants were included in the final analysis. A logistic regression model was applied to estimate the OR and 95 % CI for the prevalence of the metabolic syndrome and its components according to milk consumption. In addition, the results of our study were further meta-analysed with other published observational studies to quantify the association between the highest v . lowest categories of milk consumption and the metabolic syndrome and its components. There was no significant difference in the odds of having the metabolic syndrome between milk consumers and non-milk consumers (OR 0·86, 95 % CI 0·73, 1·01). However, milk consumers had lower odds of having elevated waist circumference (OR 0·78, 95 % CI 0·67, 0·92), elevated TAG (OR 0·83, 95 % CI 0·70, 0·99) and elevated blood pressure (OR 0·85, 95 % CI 0·73, 0·99). When the results were pooled together with other published studies, higher milk consumption was inversely associated with the risk of the metabolic syndrome (relative risk 0·80, 95 % CI 0·72, 0·88) and its components (except elevated fasting blood glucose); however, these results should be treated with caution as high heterogeneity was observed. In summary, the currently available evidence from observational studies suggests that higher milk consumption may be inversely associated with the metabolic syndrome.